PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL TERHADAP TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG INISIASI MENYUSU DINI DI PUSKESMAS JETIS, YOGYAKARTA - , ANISA RIMADHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Dissemination of information about early breastfeeding initiation in the media is not as extensive as information about exclusive breastfeeding or other issues in the health of the mother and baby while breastfeeding exclusively for 6 months has eight times more successful when preceded by early breastfeeding initiation. Objectives: To determine the effect of health education with audiovisual media in improving the knowledge and attitudes of early breastfeeding initiation and determine the level of knowledge and attitude of pregnant women about early breastfeeding initiation before and after the health education with audiovisual media in Jetis Health Center, Yogyakarta. Method: This is pilot study with one group pretest-posttest. The study was conducted in March-April 2014, with the subject of study were 15 respondents. Data were collected using a questionnaire before and one week after given intervention. Results: Knowledge of respondents gained a mean of 16.87 at the pretest for the knowledge. These results increased to 23.67 at posttest. The same is obtained in attitude. At pretest obtained a value of 32.20 and to posttest values obtained 43.06. Based on the increased value, we know that the value of p=0.00 (p <0.05) which means that there is an effect that obtained after the intervention. Conclusion: There is an effect of delivering health education about early breastfeeding initiation through the audioviusal media to increase pregnant womenâs knowledge and attitudes in Puskesmas Jetis, Yogyakarta.